World Investment Report / Transnational Corporations, Market Structure and Competition Policy - United Nations; United Nations Conference On Trade And Development (1997)
United Nations Conference on Trade and Development. Preface, Overview, Global Trends, Regional Trends, Foreign Portfolio Equity Investment, Foreign Direct Investment and Market Structure and Competition Policy, Foreign Direct Investment and Market Structure and Competition, Policy Implications, References.